Isyarat al-Qur’an Tentang Nafkah Bagi Kerabat - Afdilla Nisa; Hamdani Hamdani; Andriyaldi Andriyaldi; Syahrul Rahman (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2022)
From a number of tafsir books it is known that no mufassir views giving to relatives-what is meant by the Qur'an-is zakat. But the the opinion of the scholars of jurisprudence who allow zakat on relatives and even they consider that relatives are people who are more important than others. This study intends to know the view of the Qur'an related to the living of relatives. Therefore, the author seeks to conduct research library (library research) using the method of tafsir mawdhu'i. Based on the results of this study the authors conclude that the rights of relatives in the form of material contained in the Qur'an is not related to the issue of zakat, but the Qur'an emphasizes those who are able to provide a living to relatives in accordance with the ability.